2018
DOI: 10.1002/hep.29596
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance imaging hepatic proton density fat fraction in pediatric nonalcoholic fatty liver disease

Abstract: MRI-estimated PDFF has high diagnostic accuracy to both classify and predict histological steatosis grade and change in histological steatosis grade in children with NAFLD. (Hepatology 2018;67:858-872).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 46 publications
3
96
0
1
Order By: Relevance
“…In the phase 2 trial of OCA, an absolute 6% change in PDFF correlated with change in histological steatosis grade after treatment . Similarly, in a pediatric treatment trial, changes in PDFF correlated with histological changes . A treatment trial with ezetimibe showed that histological responders had a significant decrease in PDFF, and a secondary analysis of these data showed that an absolute reduction in PDFF by 4.1% or a relative reduction in PDFF by 29.3% (±29% [SD]) correlated with a ≥2‐point reduction in NAS, although the relatively small sample size (N = 10) and variability in PDFF among patients highlight the need for further validation of this threshold value .…”
Section: Measures Of Nash Severity and Changes In Nash Severitymentioning
confidence: 95%
“…In the phase 2 trial of OCA, an absolute 6% change in PDFF correlated with change in histological steatosis grade after treatment . Similarly, in a pediatric treatment trial, changes in PDFF correlated with histological changes . A treatment trial with ezetimibe showed that histological responders had a significant decrease in PDFF, and a secondary analysis of these data showed that an absolute reduction in PDFF by 4.1% or a relative reduction in PDFF by 29.3% (±29% [SD]) correlated with a ≥2‐point reduction in NAS, although the relatively small sample size (N = 10) and variability in PDFF among patients highlight the need for further validation of this threshold value .…”
Section: Measures Of Nash Severity and Changes In Nash Severitymentioning
confidence: 95%
“…However, it is technically demanding, time‐consuming, and potentially erroneous, as it typically samples only a small portion of the liver compared with the latter. Given this, CSE‐MRI that rapidly covers the entire liver with a refined pulse sequence corrects for T 1 bias, T 2 * decay, and spectral complexity of fat is gaining popularity as the method of choice for quantifying hepatic steatosis in response to pharmaceutical treatment in clinical trials …”
mentioning
confidence: 99%
“…Given this, CSE-MRI that rapidly covers the entire liver with a refined pulse sequence corrects for T 1 bias, 10 T 2 * decay, 11 and spectral complexity of fat 12 is gaining popularity as the method of choice for quantifying hepatic steatosis in response to pharmaceutical treatment in clinical trials. [13][14][15][16][17] For a new metric to be adopted as a robust quantitative imaging biomarker (QIB), several key performance components need to be assessed beforehand, as proposed by the Radiological Society of North America Quantitative Imaging biomarker Alliance (QIBA): linearity, bias, and precision. 18,19 Linearity is the ability of QIB to deliver measured values that are directly proportional to true values, while bias is the difference between the mean of QIB measurements and true values.…”
mentioning
confidence: 99%
“…Several studies have validated the use of MRI‐PDFF to quantify hepatic fat against both histology‐determined steatosis grade and MRI spectroscopy fat quantification . A recent study assessed the performance of MRI‐PDFF in 110 children with biopsy‐proven NASH and demonstrated excellent accuracy in classifying mild steatosis versus moderate/severe steatosis with an area under the receiving operator characteristic curve of 0.87 …”
Section: Differences Between Pediatric and Adult Nafldmentioning
confidence: 99%
“…(27)(28)(29)(30) A recent study assessed the performance of MRI-PDFF in 110 children with biopsy-proven NASH and demonstrated excellent accuracy in classifying mild steatosis versus moderate/ severe steatosis with an area under the receiving operator characteristic curve of 0.87. (31)…”
Section: Noninvasive Diagnostic Testsmentioning
confidence: 99%